2015
DOI: 10.1177/1535370215598402
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine enhances stem cell antigen-1 expression in cigarette smoke extract-induced emphysema in animal model

Abstract: Stem cell antigen-1 (Sca-1) is a mouse glycosyl phosphatidylinositol-anchored protein and a cell surface marker found on hematopoietic stem cells (HSCs). Despite decades of study, its biological functions remain little known. Sca-1 is a typical marker of bone marrow-derived HSCs, it is also expressed by a mixture of tissue-resident stem, progenitor cells in nonhematopoietic organs. Endothelial progenitor cell (EPC) is a subtype of HSC and contributes to endothelial repair by homing in on locations of injury. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…Lung function was measured using a small animal spirometer (PLY3211 system; Buxco Electronics, Sharon, CT, USA) as previously described with a minor modification . Briefly, each mouse was weighed, anesthetized by intraperitoneal injection of 10% chloral hydrate (3 ml/kg BW) and tracheostomized.…”
Section: Methodsmentioning
confidence: 99%
“…Lung function was measured using a small animal spirometer (PLY3211 system; Buxco Electronics, Sharon, CT, USA) as previously described with a minor modification . Briefly, each mouse was weighed, anesthetized by intraperitoneal injection of 10% chloral hydrate (3 ml/kg BW) and tracheostomized.…”
Section: Methodsmentioning
confidence: 99%
“…Mononuclear cells (MNCs) from the bone marrow of C57BL/6J mice were isolated via Ficoll density gradient centrifugation (Histopaque-1083, Sigma, Santa Clara, CA, USA) before being inoculated into culture flasks at a density of (3~5)×10 6 /ml and cultured with EGM-2 in 5% FBS (SingleQuots ® , Lonza, Basel, Switzerland) under an atmosphere of 95% humidity and 5% CO 2 at 37°C [ 15 ]. On day 4 of the culture, the culture fluid was replaced with fresh culture medium to remove the unattached cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cell harvesting was performed on day 7 of the culture. Double-positive staining of Ulex europaeus agglutinin-1(UEA-1) lectin and acetylated low-density lipoprotein (acLDL) was used for EPCs identification [ 15 ]. Briefly, the harvested cells were incubated with 7.5 μg/ml 1,1′-dioctadecyl-3,3,3′,3-tetramethylindocarbocyanine perchlorate(Dil)-labeled acLDL (Dil-acLDL, Molecular Probes, Eugene, OR, USA) at 37°C for 4 h and fixed with 4% paraformaldehyde for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the bioinformatics directly we can ascertain if there are CG dinucleotides in the Sca-1 promoter sequence ( http://www.urogene.org/ methprimer/). In terms of previous experiments, it was suggested that the regulation of methylation may participate in Sca-1 expression 23 . Decitabine (Dec) is a demethylation reagent and widely used in medical treatment, it can activate demethylation in vitro and in vivo 24 and make epigenetic silencing genes reactivate again 25 .…”
Section: Introductionmentioning
confidence: 87%